PENERAPAN HASIL MODIFIKASI PERMAINAN MONOPOLI SEBAGAI MEDIA PEMBELAJARAN BERBICARA BAHASA ARAB - Rohmawati, Silfiyah (STIQ Amuntai, 2019)
This study is purposed to describe the result application of monopoly game modification as a learning media of Arabic speaking in Program for Arabic Language Development (PKPBA) of the State Islamic University (UIN) of Maulana Malik Ibrahim Malang. This study uses a qualitative approach with descriptive research type. The data collection techniques used are participant observation and documentation. The results of this study are in the form of steps taken by the researcher in applying result modification of monopoly game as a learning media of Arabic speaking. The activities of the game include expressing thoughts, ideas, feelings, experiences and information through telling stories and asking questions about the materials mentioned. As for the recommendations, the results of the modification of the monopoly game in this study can be applied in learning to speak Arabic, but can also be used for other language competencies, such as listening, reading and writing, and certainly with several different and adaptable game rules. The results of this study can be used as a material modification of the monopoly game that will be used by tutors or other lecturers by adjusting the material and the ability level of students. Keyword: Modifikasi, Permainan Monopoli, Media Pembelajaran, Berbicara Bahasa Arab.